Respuesta :

14(4√a5b2c4)-7ac(4√ab2)

= 14ac(4√ab2) - 7ac(4√ab2)

= 7ac(4√ab2)

answer is A. first choice

we have

[tex]14(\sqrt[4]{a^{5} b^{2} c^{4}})-7ac \sqrt[4]{ab^{2}}[/tex]

we know that

[tex]\sqrt[4]{a^{5}}=a \sqrt[4]{a}[/tex]

[tex]\sqrt[4]{c^{4}}=c[/tex]

substitute

[tex]14(\sqrt[4]{a^{5} b^{2} c^{4}})-7ac \sqrt[4]{ab^{2}}=14ac(\sqrt[4]{a b^{2}})-7ac \sqrt[4]{ab^{2}}\\ \\=(14ac-7ac) \sqrt[4]{ab^{2}}\\ \\=7ac \sqrt[4]{ab^{2}}[/tex]

therefore

the answer is

[tex]7ac \sqrt[4]{ab^{2}}[/tex]